(untitled) (Marketing Journal, 2025)
Energy efficiency today is recognized as an integral and strategically important component of economic processes. According to data published by the International Renewable Energy Agency (IRENA) in 2024, priority tasks and strategic objectives for improvin g global energy efficiency by 2030 have been outlined. Especially in developing countries, the growing energy consumption highlights the need for energy efficiency not only for ensuring economic sustainability but also for minimizing environmental impact a nd optimizing the use of natural resources. This scientific study analyzes the theoretical foundations and scientific -analytical aspects of improving energy efficiency in the industrial sectors of Uzbekistan. It examines the mechanisms for enhancing energy efficiency, the interconnection between tec hnological modernization and ecological sustainability, and develops scientifically grounded recommendations for expanding the efficient use of resources in the national economy.